Diffusion of user innovations – a firm-level survey. (1st January 2013) - Kuusisto, Arja; Kuusisto, Jari
This survey of 379 firms in Finland demonstrates that firms commonly innovate their process software, equipment and services for in-house use. The key focus of this study is the transfer of user innovations. 35% of the user innovations in our sample were shared with some other company. User innovations were primarily shared with firms that provided support to the innovation process, and with which the innovator had a prior cooperative relationship. The study further examines the diffusion of user innovations from another, complementary angle: we asked whether firms systematically aim to identify user innovations that are created by their customers. Only a fraction of firms had any systematic programme in use, while the great majority followed user innovations randomly. Finally, the firms reported many different kinds of obstacles to making use of user innovations, which we classified under six thematic categories.